Child Protection in Pornography Law in Indonesia - Faizin Sulistio (Riwayat: Educational Journal of History and Humanities, 2023)
With the advancement of technology in the form of the internet, pornographic content has become very accessible to every age including children, as a result of which it has an impact on increasing pornography crimes among the community, especially child pornography. One of the factors that causes this is because sometimes the content is on the same web page as adult pornography content. In other countries, child pornography can be punished if a person commits acts such as viewing and possessing content containing child pornography. Unlike the legal arrangements  in Indonesia, child pornography can only be punished if a person distributes or lends his child pornography content to others for commercial purposes only, in this case it does not specifically regulate the act of "viewing and possessing child pornography content" even though in other countries this act is considered reprehensible and a criminal offense. The practice of giving punishment to perpetrators of the distribution of child pornography content in Indonesia is also still limited because it turns out that in Indonesia the act is not regulated as a criminal offense. Ideal legal protection efforts in protecting children as victims of pornography can be done by harmonizing laws and regulations related to child pornography. This is because the laws and regulations governing child pornography still have formulations related to acts that are incomplete or not explained in detail so that they cannot realize justice for child victims of pornography. Because basically everyone has the right to obtain legal protection, including children. The writing of this journal uses  normative juridical aspects and uses conceptual approach methods. Meanwhile, to analyze this problem is carried out by a descriptive analysis method, which is looking for the theoretical basis of child protection in pornography law in Indonesia.